„This is truth". Edith Stein's Way to God in the Light of Hans Urs von Balthasar's Theology. - Jędraszewski, Marek (Filozofia Chrześcijańska, 2011)
The crucial moment in Edith Stein’s life was the reading of Therese from  Avila’s autobiography in 1921. Having read it, she declared this well-known sentence: Das ist die Wahrheit – „This is truth!”. In the first part the article shows Edith Stein as a person passionately and consequently searching the truth. The second part is an attempt to interpret of what the truth itself is. There is also an analysis of the meaning for Edith Stein of her confession uttered in the moment of her conversion in the light of Hans Urs von Balthasar’s theology (truth as áëçoeaéá and truth as emeth) and in consequence what the essence of her being a theological person was.